ETHERNET PHYSICAL ENVIRONMENT LIST - Meliziyayev Obbosjon Olimjon o’g’li (Bright Mind Publishing, 2025)
The first Ethernet technology network was built on a 0.5-inch diameter. Later, a physical footprint for the Ethernet stand, which can be used in other different data transmission environments, was also discovered. The definition of the optional physical environment of the CSMA/CD memory method and the existing VAQT longitudinal Ethernet 10 Mbit/s technology remains the same.
Keywords: Ethernet, physical medium, twisted pair, coaxial cable, fiber optic cable, network architecture, data transmission speed, connectors (RJ-45), maximum distance, LAN, cable types, network interface, transmission media, network topology.